ПОЛИМИНЕРАЛЬНОЕ ВКЛЮЧЕНИЕ КАК ОТРАЖЕНИЕ МИНЕРАЛОГИИ САРЫЛАХСКОГО МЕСТОРОЖДЕНИЯ - Анисимова Г.С. (My University, 2005)
The paper displays data on the unique micro inclusion, as large as 0.3 mm across, containing in close association nearly all typomorphic minerals of the unique Sarylakh gold-antimony ore deposit. A grain of quartz, prisoner in the «pig-iron» stibnite, forms a framework of polymineral inclusion with structure containing native gold of massive, spongy and mustard shape, aurostibite, arscnopyrite, sphalerite, stibnite, ullmannite, and antimony oxides. There is a detailed description of relationship between those minerals, data on their chemical compositions and some physical properties. Composition of ullmannite in Sarylakh deposit has been determined there for the first time. The studied micro-paragencsis of minerals shows the following sequence of the mineral-forming process: arsenopyrite-sphalerite-massive gold-aurostibite--ullmannite-Sb oxides-spongy and mustard gold (+stibnite).
Keywords: 553.45(571.56)